If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 139 + -3x = 6x + 22 Reorder the terms: 139 + -3x = 22 + 6x Solving 139 + -3x = 22 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 139 + -3x + -6x = 22 + 6x + -6x Combine like terms: -3x + -6x = -9x 139 + -9x = 22 + 6x + -6x Combine like terms: 6x + -6x = 0 139 + -9x = 22 + 0 139 + -9x = 22 Add '-139' to each side of the equation. 139 + -139 + -9x = 22 + -139 Combine like terms: 139 + -139 = 0 0 + -9x = 22 + -139 -9x = 22 + -139 Combine like terms: 22 + -139 = -117 -9x = -117 Divide each side by '-9'. x = 13 Simplifying x = 13
| 2x+3(x-1)=27 | | 3(1+Y)=3-(5y+2) | | -17=-5+4u | | 2-6x=10-8x | | 4j-1+7= | | 15y=14(y+16) | | 3g+3(-5+4g)=1-g | | 2x^2-7x-16=-3x | | 3x+10=45-2x | | 3(6x-4)=22x | | 3(n-1)-2=4(n-4)-(n-11) | | 2(8q-1)+3(5q+6)= | | 12=2w+2 | | 10(x-5)=9(x+5) | | 9a-4+3a-33=23 | | 2(x-3)+4x=18 | | 5y-5=-35 | | 2(x-3)+4x=6.5 | | 7x-3x-8=24 | | 9y+y+8y+2y+5y= | | 2(x-3)=6.5 | | 3(2x-10)=6(x-10) | | 12x-3=4x+93 | | 3x^2=51x | | 25=4+3y | | 8b-11+3b=121 | | 284-2x=43x+19 | | -2(y-4)=12-y | | 25x^2-49=0 | | c^2=25 | | 5xn-3=32 | | 5(y+2)+3y=50 |